Rational Design of the Platinahelicene Enantiomers for Deep-Red Circularly Polarized Organic Light-Emitting Diodes - Yan, Zhi-Ping; Luo, Xu-Feng; Liao, Kang; Zheng, You-Xuan; Zuo, Jing-Lin (Frontiers in Chemistry, 2020)
[n]Helicene derivatives are most popular chiral structures to construct luminescent materials with circularly polarized (CP) light, which have revealed appealing application in chiral optoelectronics. Particularly, because of the unique phosphorescent emission, platinahelicene have great application prospects in CP organic light-emitting diode (CP-OLED). Herein, by decorating the pyridinyl-helicene ligand with trifluoromethyl (-CF3) unit in a specific position, a pair of platinahelicene enantiomers were prepared and separated with extremely twisted structure showing not only superior thermal and configurational stability but also good CP luminescence (CPL) property with dissymmetry factors (|gPL|) of 6×10-3. Moreover, the evaporated CP-OLEDs based on platinahelicene enantiomers exhibited the deep-red emission with the peak at 653 nm as well as obvious CP electroluminescence (CPEL) signals with the |gEL| in 10-3 order. Therefore, the design strategy provides an efficient way to improve the CPL properties of platinahelicene to cope with the future application in CP-OLEDs.